Building climate-smart fisheries in Australia: insights from climate and ecosystem status reports - Stephanie Brodie; Laura K. Blamey; Alistair J. Hobday; Éva Plagányi; Daniel Corrie; Natalie Couchman; Alice McDonald; Campbell Davies; Ryan A. Downie; J. Paige Eveson; Elizabeth A. Fulton; Jason R. Hartog; et al. (Reviews in Fish Biology and Fisheries, 2026)
Ongoing concerns about the impact of climate change on Australia’s oceans has driven a request from fisheries managers for improved science communication to the seafood sector. Despite these concerns, translating climate science into management and industry action at regional and sectoral scales remains a challenge. We developed a reporting structure for communicating climate and ecosystem status to fisheries management, industry, and research stakeholders. Our reports consider historical climate impacts, ecosystem indices derived from scientific observing programs, anecdotal on-the-water observations from industry, and forecast climate outlooks tailored for the upcoming fishing season. We developed and delivered reports across 10 diverse fishery case studies, spanning multiple spatial scales and regions (from the tropical north to the temperate south and sub-Antarctic islands) and target species (encompassing benthic invertebrates, demersal fish and sharks, and pelagic billfish and tunas). Here, we describe the reporting structure, the climate and ecosystem indices used, as well as key lessons from the development and dissemination of reports. Key lessons include: (1) Developing tailored environmental indices enhances relevance; (2) Ecosystem observations are essential but remain spatially and temporally patchy; (3) Fishery-independent surveys provide vital data; (4) Remote climate drivers must be considered; (5) Seasonal forecasts offer actionable insights for short-term planning; (6) Fisher observations provide context-rich information that should be systematically incorporated. The lessons and general reporting structure can be applied to the development of other climate and integrated ecosystem reporting activities that are ongoing around the world. We contend that these reports serve as important tools for fostering climate resilience and facilitating the adaptation of the Australian seafood sector to the short and long-term challenges of rapidly changing ocean ecosystems.

Acceptable intakes (AIs) for 11 small molecule N-nitrosamines (NAs) - Joel P. Bercu; Melisa Masuda-Herrera; Alejandra Trejo-Martin; Priyanka Sura; Robert Jolly; Michelle Kenyon; Rob Thomas; David J. Ponting; David Snodin; Gregor Tuschl; Stephanie Simon; Kathleen De Vlieger; et al. (Regulatory Toxicology and Pharmacology, 2023)